PjBL-STEAM approach to enhance students’ creativity and science process skills in biology learning - Avarha Mahaputri Jasmine Novarman; Supriyatin Supriyatin; Rusdi Rusdi (Biosfer: Jurnal Pendidikan Biologi, 2026)
The advancement of knowledge and technology in the globalization period has had a significant impact on various aspects of life, the most notable of which is the educational sector.  A comprehensive learning plan is required for the 21st century.  The learning model is one of the critical components of learning that promotes active and interactive participation among students. Using an appropriate learning paradigm, a variety of experiences for students can be maximized.  This study aims to examine the effect of the PjBL learning model with the STEAM approach on students' creative thinking skills and science process skills on environmental pollution material. This study was conducted at SMAN 112 Jakarta, Indonesia in class X. This research method is quasi-experimental with a quasi-experimental research design with multiple control groups. The total number of selected samples is 132 students. Based on the hypothesis test using MANOVA, there is an effect of the PjBL-STEAM learning model on students' creative thinking skills and science process skills (p <0.05), so that the findings indicate that the PjBL-STEAM learning model has been proven to significantly influence students' creative thinking skills and science process skills in class X, on environmental pollution material.